Implementation of the Non-Cash Food Assistance Program in Sidoarjo Regency - Nur Rochmah Yulia Safitri; Isnaini Rodiyah (Indonesian Journal of Public Policy Review, 2022)
This study aims to determine the implementation of the non-cash food assistance program in Pucang Village, Sidoarjo District, Sidoarjo Regency, and to determine the supporting factors and inhibiting factors for the implementation of the non-cash food assistance program in Pucang Village, Sidoarjo District, Sidoarjo Regency. This research uses descriptive qualitative research method. Data collection techniques using observation, interviews, and documentation. Data analysis techniques using Miles and Huberman are data collection, data reduction, data presentation and conclusion drawing. The results showed that the implementation of the non-cash food assistance program in Pucang Village in terms of communication, socialization activities went smoothly and KPM already understood the BPNT program, in terms of resources, officers were experts in running the program, in terms of disposition, officers supported and committed to implementing the program. program, but KPM complained that the recipients of BPNT assistance were still not properly targeted because there were still many poor people who had not received assistance, there was also a zero balance in the KPM account, as well as the EDC machine that experienced disturbances/errors and in terms of the bureaucratic structure, the program was in accordance with the regulations. . There are supporting factors in the implementation of BPNT, namely experienced human resources and the availability of e-warong places and inhibiting factors for program implementation, namely zero balance, EDC machines are experiencing problems, and inaccuracy in the distribution of aid. Keywords - Policy Implementation; Non-Cash Food Assistance; and e-warong